2016
DOI: 10.3945/jn.115.224402
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cell Depletion Abolishes the Protective Effect of Dietary Galacto-Oligosaccharides on Eosinophilic Airway Inflammation in House Dust Mite–Induced Asthma in Mice

Abstract: Treg depletion enhances pulmonary type 2 T helper cell frequency and cytokine release in HDM-induced asthma in mice. Galacto-oligosaccharides decreased airway eosinophilia and IL-33 concentrations in the lung, which was abrogated by Treg depletion. This indicates that galacto-oligosaccharides have a beneficial effect in the prevention of HDM-induced allergic asthma by supporting pulmonary Treg function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…After 2'FL and 6'SL treatment during challenge in ovalbumin sensitized mice enhanced the capacity of CD4+CD25+ T reg cells to inhibit mast cell degranulation ex vivo (39), indicating that specific sHMOS support T reg cell function. Similar results were found using scGOS and lcFOS in combination with acidic oligosaccharides or B. breve in prevention of food- (29,166) or asthma-allergy in mice (31,165). In piglets, either sow-reared or formula fed, peripheral blood mononuclear cells (PBMCs) were isolated (164).…”
Section: Hmos Interact With Immune Cellssupporting
confidence: 62%
“…After 2'FL and 6'SL treatment during challenge in ovalbumin sensitized mice enhanced the capacity of CD4+CD25+ T reg cells to inhibit mast cell degranulation ex vivo (39), indicating that specific sHMOS support T reg cell function. Similar results were found using scGOS and lcFOS in combination with acidic oligosaccharides or B. breve in prevention of food- (29,166) or asthma-allergy in mice (31,165). In piglets, either sow-reared or formula fed, peripheral blood mononuclear cells (PBMCs) were isolated (164).…”
Section: Hmos Interact With Immune Cellssupporting
confidence: 62%
“…HDM sensitization and challenge did not affect the frequency of Treg and budesonide treatment tended to lower the %Treg which could not be rescued by the dietary intervention with GOS. However, in a previous study GOS was shown to improve the regulatory function of the CD25+ cells, which include Treg and via this way GOS may have supported the anti-inflammatory capacities of budesonide treatment ( 68 ).…”
Section: Discussionmentioning
confidence: 97%
“…While there is evidence that supplementing diets with certain nondigestible oligosaccharides can reduce the incidence of allergic disease in children (Gruber et al., ; Moro et al., ) and attenuate symptoms of allergy in animal models (Castillo‐Courtade et al., ; Hogenkamp, Knippels, Garssen, & van Esch, ; Schouten et al., ; Verheijden et al., , ) the mechanisms of action have yet to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%